Biexcitons in solid neon - Wiethoff, P.; Kassühlke, B.; Menzel, D.; Feulner, P. (Физика низких температур, 2003)
We study the creation of biexcitons in neon films on a metal substrate by one-photon processes. We demonstrate that photon stimulated desorption of ions is a perfect tool for the investigation of these excitation processes which possess very low cross sections. We show that the principle of the equivalent core approximation which is well know from inner shell experiments can also be applied to the neon biexciton case. Comparing the equivalent core molecules Ne₂** and Na₂ we find that neon biexcitons can be well described in a Frenkel picture.